2021
DOI: 10.1182/blood.2020008727
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib, obinutuzumab, and venetoclax in relapsed and untreated patients with mantle cell lymphoma: a phase 1/2 trial

Abstract: Ibrutinib, obinutuzumab plus venetoclax demonstrate synergy in pre-clinical models of mantle-cell lymphoma (MCL). OAsIs (NCT02558816), a single-arm multi-center prospective phase I/II trial, aimed to determine the maximum tolerated dose (MTD) of venetoclax in combination with fixed doses of ibrutinib and obinutuzumab, in relapsed MCL patients. At the venetoclax MTD, extension cohorts were opened for relapsed and untreated patients. Safety and efficacy were secondary objectives. Minimal residual disease (MRD) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 26 publications
3
92
0
2
Order By: Relevance
“…Our approach was novel in finding the optimal dose, instead of the maximum tolerated dose, utilizing a CRM to allocate participants based on prior participant's efficacy and toxicity. Our primary finding shows that the optimal dose was Arm B (IBR 420mg PO daily, VEN 200mg PO daily), which is lower than other studies are using (SYMPATICO study, NCT03112174) 33,34 or have used (AIM or OAsIs study) 28,29,35 in relapsed MCL. The SYMPATICO 33,34 , AIM 28,35 , and OAsIs 29 studies utilize IBR 560mg PO daily and VEN 400mg PO daily in MCL, a dose combination that we were not able to test due to DLTs and adequate response at lower dose levels.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Our approach was novel in finding the optimal dose, instead of the maximum tolerated dose, utilizing a CRM to allocate participants based on prior participant's efficacy and toxicity. Our primary finding shows that the optimal dose was Arm B (IBR 420mg PO daily, VEN 200mg PO daily), which is lower than other studies are using (SYMPATICO study, NCT03112174) 33,34 or have used (AIM or OAsIs study) 28,29,35 in relapsed MCL. The SYMPATICO 33,34 , AIM 28,35 , and OAsIs 29 studies utilize IBR 560mg PO daily and VEN 400mg PO daily in MCL, a dose combination that we were not able to test due to DLTs and adequate response at lower dose levels.…”
Section: Discussionmentioning
confidence: 72%
“…We present the only known phase I dose-finding study of IBR and VEN in NHL that evaluates dosing of both drugs. Prior clinical studies 28,29 of the IBR and VEN combination have utilized the single-agent approved doses in combination as Phase II studies or have attempted to increase the approved doses in phase I study. Our approach was novel in finding the optimal dose, instead of the maximum tolerated dose, utilizing a CRM to allocate participants based on prior participant's efficacy and toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…© 2021 American Association for Cancer clincancerres.aacrjournals.org Downloaded from Author manuscripts have been peer reviewed and accepted for publication but have not yet been edited. Author Manuscript Published OnlineFirst on June 3, 2021; DOI: 10.1158/1078-0432.CCR-20-4842 MCL(19), and if positive, would extend the initial benefits seen in this study with venetoclax monotherapy to a much larger proportion of patients with NHL.…”
mentioning
confidence: 66%
“…A wide range of combination treatment approaches have been previously studied for relapsed MCL, with selected results from previously published trials shown in Table 1 [16,[73][74][75][76][77]. The combination of ibrutinib and rituximab was studied in a phase 2 trial enrolling 50 patients with r/r MCL and demonstrated an ORR of 88% (44%) with more favorable response rate noted in patients with Ki67 < 50% (ORR 100%, 54% CR) compared with high-risk patients with Ki67 ≥ 50% (ORR 50%, 17% CR) [16].…”
Section: Combinationsmentioning
confidence: 99%